Successive silencing of tandem reporter genes in potato (Solanum tuberosum) over 5 years of vegetative propagation - Nocarova, Eva; Opatrny, Zdenek; Fischer, Lukas (Annals of botany, 2010)
BACKGROUND AND AIMS: Transgenic plants represent an excellent tool for experimental plant biology and are an important component of modern agriculture. Fully understanding the stability of transgene expression is critical in this regard. Most changes in transgene expression occur soon after transformation and thus unwanted lines can be discarded easily; however, transgenes can be silenced long after their integration. METHODS: To study the long-term changes in transgene expression in potato (Solanum tuberosum), the activity of two reporter genes, encoding green fluorescent protein (GFP) and neomycin phosphotransferase (NPTII), was monitored in a set of 17 transgenic lines over 5 years of vegetative propagation in vitro. KEY RESULTS: A decrease in transgene expression was observed mainly in lines with higher initial GFP expression and a greater number of T-DNA insertions. Complete silencing of the reporter genes was observed in four lines (nearly 25 %), all of which successively silenced the two reporter genes, indicating an interconnection between their silencing. The loss of GFP fluorescence always preceded the loss of kanamycin resistance. Treatment with the demethylation drug 5-azacytidine indicated that silencing of the NPTII gene, but probably not of GFP, occurred directly at the transcriptional level. Successive silencing of the two reporter genes was also reproduced in lines with reactivated expression of previously silenced transgenes. CONCLUSIONS: We suggest a hypothetical mechanism involving the successive silencing of the two reporter genes that involves the switch of GFP silencing from the post-transcriptional to transcriptional level and subsequent spreading of methylation to the NPTII gene.
Keywords: regulace genové exprese u rostlin; Green Fluorescent Proteins; DNA Methylation; umlčování genů; geneticky modifikované rostliny; kanamycinkinasa; transgeny; Gene Silencing; Plants, Genetically Modified; zelené fluorescenční proteiny; Transgenes; Gene Expression Regulation, Plant; Kanamycin Kinase; metylace DNA; Solanum tuberosum